Managerial competences in public organisations: the healthcare professionals' perspective - Simone Fanelli; Gianluca Lanza; Cristiana Enna; Antonello Zangrandi (BMC, 2020)
Abstract Background Human resources play a critical role in encouraging efficient performance within organisations, especially for public healthcare organisations, where competences of staff are key aspects of the quality of services provided. In this context, the enhancement of competences are strategic objectives for Human Resources Management (HRM) in order to achieve excellent and lasting results. However, competences of healthcare professionals are both clinical and managerial. This study identifies specific managerial competences perceived as crucial by healthcare professionals in order to improve their performance and develop suitable HRM practices. Methods The research methodology was divided into three main phases using mixed methods, commencing with literature review to identify the initial framework about managerial competences. Focus groups were then used to discuss evidence from the literature. Feedback from focus groups was used to draft the final questionnaire. Finally, the answers to the questionnaire were analysed through statistical software. Results The results show that managers and professionals share a view of what specific managerial competences for healthcare organisations should be. Main competences are: quality evaluation based on outcomes; enhancement of professional competences; programming based on process management; project cost assessment; informal communication style; and participatory leadership. Conclusions Although the issue of managerial skills in healthcare is widely discussed in literature, findings are often fragmentary. Our work includes a systematic literature review useful for more empirical studies. Furthermore, our results can support public managers who want to set up positive HRM practices for healthcare professionals.